THE CLASSIFICATION OF TOTAL QUALITY MANAGEMENT IMPLEMENTATION IN GUEST HOUSES - Fauzan Robbani, Muhammad (Manajemen Bisnis, 2019)
This study aims to find out and analyze the classification of guest houses based on TQM implementation in Klojen Sub-district, Malang. The analytical method used was cluster analysis with 18 guest houses as the research objects and 22 statements about TQM in the questionnaire. The results showed that there were two groups of guest houses formed based on the TQM implementation. The first group was the guest house group which had theoritical TQM implementation and a vision. This group was also oriented to quality with good Human Resources who were given a freedom to be involved in it, and they constantly made continuous improvements focusing on the consumers? wants and needs. Meanwhile, group 2 was the guest house group with TQM implementation which was built with strong teamwork and long-term commitment to implement it. For both groups, it is important to maintain the strong TQM variables and to improve the TQM variables that have not been implemented.